(untitled) (قضايا سياسية, 2025)
Ambassadors usually are expected to represent their states at other countries and defend their interests ,the representation of the American ambassadors in Iraq shouldn't be different ,but most of the ambassadors who were in charge post 2003 raised controversies in the policies followed by them ,and considered as intervention in the internal affairs of the country ,surpassing the usual tasks of the ambassadors .They have impunities and privileges that help them in their mission but at the same time there are cautions and ristrictions that they should not override .So the research is trying to discover whether the American ambassadors in Iraq have worked according to the same pattern or differed in their behavior according to the persons themselves ,the time of their tenure ,and their relationships ,all of this in a historic and comparative approach .